Analisis Faktor Penentu Tingkat Kepatuhan Membayar Zakat (Studi pada BAZNAS DKI Jakarta) - Muthi'ah, Shofiyatul; Beik, Irfan Syauqi; Endri, Endri (ILTIZAM Journal of Shariah Economics Research, 2021)
Indonesia’s economic growth in 2017 reached 5.07% higher than the 2016 achievement of 5.03% according to Statistics Indonesia. Further, the economic structure also improved indicated by the high investment. However, this economic growth has not been enjoyed and improved the welfare of people as a whole and evenly. In September 2017, Statistics Indonesia noted that there were 26.58 million of the total Indonesian population who lived below poverty line. This showed that there are still many Indonesians who have not been prosperous. Zakat is integral part of Islam and become social safety net. The potential of zakat in Indonesia according to the results of BAZNAS and IPB research is estimated at 217 trillion rupiah every year, however the real zakat collection by BAZNAS and other zakat institutions have not close to these figures. This showed that there are Muslims who are reluctant to pay zakat. Research conducted by Mukhlis & Beik stated the factors that affect compliance level of paying zakat are religious factors such as faith, religious understanding and rewards; and other factors such as social awareness, self – satisfaction and organization. Based on the background above, the researcher wants to know the factors that affect compliance level of paying zakat in Jakarta City as the case study. This research was conducted with a survey of 200 respondents and employ logistic regression analysis. The results showed the factors that affect compliance level of paying zakat are factors the religious understanding, self satisfaction and organization while other known factors have no significant influence. Keywords: zakat, compliance, logistic regression